1994
DOI: 10.21273/hortsci.29.7.726d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization of Sweet Potato and Its Effect on Hoot Set and Yield

Abstract: In preplant nitrogen studies with the `Beauregard' Variety maximum yields of U.S. No. 1 grade roots are produced using 50.4 kg/ha N. In 1992 studies were initiated to determine the effect of preplant N rates on storage root set and yield. Preplant N rates ranged from 0 to 84 kg/ha in 16.8 kg/ha increments. Two plots each of 0, 16.8 and 33.6 kg/ha were included so sidedress applications could be made to bring one of the treatments to the 50.4 kg/ha N level 30 days after transplanting. The 0 kg/ha N trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results from our work coincide with field plot data regarding N rate effects on SR yield in 'Beauregard,' particularly in the southeastern U.S. production regions. Mulkey at al. (1994) reported that the maximum yield of 'Beauregard' U.S. No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from our work coincide with field plot data regarding N rate effects on SR yield in 'Beauregard,' particularly in the southeastern U.S. production regions. Mulkey at al. (1994) reported that the maximum yield of 'Beauregard' U.S. No.…”
Section: Discussionmentioning
confidence: 99%
“…In Louisiana, sweetpotato growers commonly use urea or urea-containing fertilizers (Cannon, personal communication). The N rate of 50 kg · ha -1 has been documented by previous work as optimum for 'Beauregard' in Louisiana (Mulkey et al, 1994). The second set of experiments used a split-root culture system (SPLIT ROOT) ( Fig.…”
Section: Methodsmentioning
confidence: 99%